Family dynamics and infants' use of media - Abadilla, Paulina Marie T.; Tanchuling, Marie Elena Assumpta M.; Jamero, Josephine Louise F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
Little is known about the way infants use screen media within the context of their families of origin. The following qualitative study addresses this research gap by defining the family dynamics of Filipino families by using the FACES IV questionnaire and the Circumplex Model of Marital Systems and Family Relations as a preliminary step to describing how infants within each family type use screen media. The data was attained from the participation of 30 respondents. These respondents were asked to complete the FACES Questionnaire, a pre interview form and an interview. Based on the data gathered, two specific family types emerged from the sample 15 Mid Range and 15 Balanced. Although the sample is equally distributed between the two family types, this was purely coincidental. As the patterns from the interviews of each family type were observed, the data shows that these two family types are slightly distinct from one another but possess many similarities. The distinctions of these two family types lie mainly in their family dynamics. But despite their differences, the data shows that they have many similar uses for screen media for their infants. To discuss these concepts objectively, the following study considers the different uses, levels of accessibility, media content, physical use, and family media time for different devices.
submitted June 2017
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Families -- Philippines; Mass media and children -- Philippines